Brain, behavior and epigenetics - Petronis, Arturas; Mill, Jonathan (Springer ebooks., 2011)
Despite significant progress in molecular epigenetic research and its enormous potential, there are still considerable challenges to overcome before we can fully understand the role of epigenetic processes in brain function and behavior. For instance, what comprises a ?normal? brain epigenome and what is the degree of region- and cellular-specificity of epigenetic landscapes in the brain? How do the multiple layers of epigenetic information interact and change over time? How common is meiotic epigenetic heritability and what role it may play in complex psychiatric disease? To what extent is the epigenome plastic and malleable in response to environmental influences? This volume demonstrates that such questions can now be explored in an experimental molecular biology laboratory. While the community is only just starting to acknowledge the importance of epigenetic processes in the brain, there is no doubt that numerous breakthrough discoveries in brain and behavioral epigenetics will be made